Pore size control in activated carbons obtained by pyrolysis under different conditions of chemically impregnated cork - Carrott, P. J. M.; Ribeiro Carrott, M. M. L.; Mourão, P. a M. (Journal of Analytical and Applied Pyrolysis, 2006)
Activated carbons were prepared by the pyrolysis of cork impregnated with potassium and sodium hydroxides and carbonates as well as phosphoric acid and the effect of ﬁve experimental parameters, namely method of impregnation, impregnant concentration, mass ratio, precursor particle size and pyrolysis temperature, were studied. It is shown that cork is a versatile precursor and allows us to prepare a wide variety of materials with quite different pore structural characteristics by precise control of the impregnation and pyrolysis conditions. Even under relatively mild conditions, it was possible to produce cork based carbons with high pore volumes, in the range 0.5–0.7 cm 3 g 1 , and to simultaneously control the mean pore width over a three-fold range from a value as low as 0.7 nm up to a value as high as 2.2 nm. The best materials produced present pore structural characteristics which are signiﬁcantly different to the vast majority of commercial activated carbons. In particular, the possibility of obtaining such high pore volumes in essentially microporous materials, containing virtually no mesoporosity in most cases, is noteworthy. Furthermore, the fact that it was possible with some samples to combine high pore volume and very narrow micropore size is a particularly notable achievement.
Keywords: activated carbon; chemical activation; Cork; microporosity